Genetic lineages of undifferentiated-type gastric carcinomas analysed by unsupervised clustering of genomic DNA microarray data - Sonoda, Ayano (BioMed Central, 2013)
BACKGROUND: It is suspected that early gastric carcinoma (GC) is a dormant variant that rarely progresses to advanced GC. We demonstrated that the dormant and aggressive variants of tubular adenocarcinomas (TUBs) of the stomach are characterized by loss of MYC and gain of TP53 and gain of MYC and/or loss of TP53, respectively. The aim of this study is to determine whether this is also the case in undifferentiated-type GCs (UGCs) of different genetic lineages: one with a layered structure (LS+), derived from early signet ring cell carcinomas (SIGs), and the other, mostly poorly differentiated adenocarcinomas, without LS but with a minor tubular component (TC), dedifferentiated from TUBs (LS−/TC+). METHODS: Using 29 surgically resected stomachs with 9 intramucosal and 20 invasive UGCs (11 LS+ and 9 LS−/TC+), 63 genomic DNA samples of mucosal and invasive parts and corresponding reference DNAs were prepared from formalin-fixed, paraffin-embedded tissues with laser microdissection, and were subjected to array-based comparative genomic hybridization (aCGH), using 60K microarrays, and subsequent unsupervised, hierarchical clustering. Of 979 cancer-related genes assessed, we selected genes with mean copy numbers significantly different between the two major clusters. RESULTS: Based on similarity in genomic copy-number profile, the 63 samples were classified into two major clusters. Clusters A and B, which were rich in LS+ UGC and LS−/TC+ UGC, respectively, were discriminated on the basis of 40 genes. The aggressive pattern was more frequently detected in LS−/TC+ UGCs, (20/26; 77%), than in LS+UGCs (17/37; 46%; P = 0.0195), whereas no dormant pattern was detected in any of the UGC samples. CONCLUSIONS: In contrast to TUBs, copy number alterations of MYC and TP53 exhibited an aggressive pattern in LS+ SIG at early and advanced stages, indicating that early LS+ UGCs inevitably progress to an advanced GC. Cluster B (enriched in LS−/TC+) exhibited more frequent gain of driver genes and a more frequent aggressive pattern than cluster A, suggesting potentially worse prognosis in UGCs of cluster B.